Forces that Prevent Agile Adoption in the Automotive Domain - Hohl, Philipp; Münch, Jürgen; Schneider, Kurt; Stupperich, Michael (Product-Focused Software Process Improvement, 2016)
Context: The current transformation of automotive development towards innovation, permanent learning and adapting to changes are directing various foci on the integration of agile methods. Although, there have been efforts to apply agile methods in the automotive domain for many years, a wide-spread adoption has not yet taken place. Goal: This study aims to gain a better understanding of the forces that prevent the adoption of agile methods. Method: Survey based on 16 semi-structured interviews from the automotive domain. The results are analyzed by means of thematic coding. Results: Forces that prevent agile adoption are mainly of organizational, technical and social nature and address inertia, anxiety and context factors. Key challenges in agile adoption are related to transforming organizational structures and culture, achieving faster software release cycles without loss of quality, the importance of software reuse in combination with agile practices, appropriate quality assurance measures, and the collaboration with suppliers and other disciplines such as mechanics. Conclusion: Significant challenges are imposed by specific characteristics of the automotive domain such as high quality requirements and many interfaces to surrounding rigid and inflexible processes. Several means are identified that promise to overcome these challenges.